Inner ear therapeutics and the war on hearing loss: systemic barriers to success - Jiam, Nicole T.; Rauch, Steven D. (Frontiers in Neuroscience, 2023)
Despite over 20 years of effort in academic research centers, start-up companies, and established pharmaceutical companies, there are no FDA-approved inner ear therapeutics for treatment of sensorineural hearing loss. There are a number of systemic barriers to creation of this new field of inner ear therapeutics. These include insufficient understanding of the particularity of different causes of hearing loss at the cellular and molecular level, lack of diagnostics of adequate sensitivity and specificity to discern these differences in vivo, a tendency for start-up biotech/pharma companies to prioritize competition over collaboration, and a drug development ecosystem that is really in the “pre-competitive” phase and lacking the infrastructure to develop, validate, gain regulatory approval, and successfully market an inner ear therapeutic. These issues will be discussed and a proposed remedy in the form of an inner ear therapeutics “moon shot” will be offered.